AUDIENCE'S INTERPRETATION OF GOJEK YOUTUBE ADS #BEFORE GOJEK BUYS URGENT GOODS, THE TRIP IS LONG, GO-MART-IN AJA! - Irish Ade Pertiwi; Rizky Oktarina Costa (Media Inovasi Pendidikan dan Publikasi, 2023)
Gojek's flagship services are food ordering and shopping. Shopping service is called GOMART. This service is synonymous with more efficient and faster shopping. In its development, Gojek uses social media in communicating its messages to the public, especially Youtube social media as the largest user platform in Indonesia. Gojek Advertisement Go Mart Edition Version #BeforeGojek Buy Urgent Goods Long Trip, GoMart-in Aja! is one of the advertisements that uses the Youtube Platform and can be seen at https://www.youtube.com/watch?v=Oqd8PJCb–o. The focus and purpose of this research is to analyze how audiences assess and interpret the content of this advertising message using Stuart Hall's reception analysis to produce three forms of message interpretation, namely: Dominant Hegemonic Position, Negotiated Position, and Oppositional Position. The research is a descriptive qualitative research with 8 informants. Humor and moral advertisements that have concepts close to everyday life are packaged into storytelling to attract audiences, considered more interesting to introduce a product to the public for now; General audience reception when watching Gojek advertisements Go mart edition version #SebelumGojek explains that the audience sees from the side of humor and morals related to the circumstances of everyday life, such as the appearance of a mother and child, the transformation of property such as motorbikes and children's clothes that change to the position of the child who was originally in the stroller by his mother and when he arrived home carrying the diaper, the mother's position was already in a wheelchair, making this ad flow a reminder of the informant to his mother, and the informant assessed this ad out of the box; Audience reception of the meaning of the content of advertising messages, generally divided into three categories, namely: a). Dominant Hegemony, namely the advertising messages conveyed in the Gojek edition of the Go Mart version of #SebelumGojek which they interpret are related to values, social norms, culture in everyday life where the audience's interpretation of filial piety to parents throughout the ages and the role of technology in shopping for their needs with the existence of Go Mart. b). Negotiation, where the advertising message conveyed is less directly accepted by the audience and they provide other meanings, for example, a role of technology and a prominent element of humor. c).Opposition, where the advertising message conveyed in the advertisement does not focus on marketing the features of Gojek and this advertisement is rambling.